Pengaruh Perputaran Kas, Perputaran Persediaan Dan Perputaran Piutang Terhadap Profitabilitas Perusahaan Manufaktur Subsektor Tekstil dan Garmen Periode 2018-2023 - Herlina Puspita Sari; Dian Nirmala Dewi; Arif Makhsun (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research aims to analyze cash turnover, receivables turnover and inventory turnover on profitability in textile and garment subsector companies listed on the Indonesia Stock Exchange (BEI) for the period 2018 to 2023. This research uses quantitative methods. The population of this research is all textile and garment subsector manufacturing companies listed on the IDX. The sample in this study used purposive sampling totaling 16 textile and garment subsector manufacturing companies listed on the IDX. The data collection technique in this research uses secondary data. Data analysis used the classic assumption test, then multiple linear regression analysis was carried out, and continued with hypothesis testing using the SPSS version 25 software program. The results of this research show that cash turnover and accounts receivable turnover have no effect on profitability. Meanwhile, inventory turnover affects profitability. Simultaneously cash turnover, accounts receivable turnover and inventory turnover together influence profitability